The Triple Helix Theory as a Solution for the Unification of the Hijri Calendar in Indonesia - Fitriyanti, Vivit; Haries, Akhmad; Syakur, Abd (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
The Islamic calendar system is an important element of Islamic civilization, but its uniform implementation across the Muslim world, including Indonesia, remains a challenge. Despite Indonesia's Muslim majority, differences persist in determining the start and end of months in the Hijri calendar. Various efforts to establish a unified Islamic calendar have not yet succeeded. This study, titled